Quality of Life and Age-Related Predictor Symptoms in Breast Cancer Survivors Undergoing Hormone Therapy: A Study from the Northern Region of Morocco - Fadoua El Battioui; Abdelouahid Louazi; Noura Boukil; Zohra Ben Allal; Rajae Alloudane; Said Barrijal (European Journal of Breast Health)
Objective: The aim of this study was to assess the health-related quality of life (HRQoL) of breast cancer (BC) survivors during adjuvant hormone therapy (AHT) as a function of age and to identify predictor symptoms. Materials and Methods: The study was based on a cross-sectional survey of 216 BC survivors undergoing AHT, in the Northern Region of Morocco. HRQoL was assessed using a validated HRQoL questionnaire, the Functional Assessment of Cancer Treatment (FACT-ES). Multiple linear regression analysis was used to identify predictor symptoms for the subscales of the FACT-ES. Results: Younger women (<45 years) had lower scores on the emotional well-being subscale (p = 0.021). Irritability (b: -0.786; p = 0.001) and mood swings (b: -0.835; p = 0.031) were the strongest negative predictors of emotional quality of life. In both age groups, items related to social support had a positive effect on survivors’ social HRQoL (p<0.05). Conclusion: BC survivors’ HRQoL during AHT differed by age group. Emotional problems negatively influenced HRQoL in younger women. Knowledge of the symptoms that predict HRQoL in BC survivors may help clinicians develop personalized interventions.